The Analysis of Popularity of Depression and Anxiety Related to Social Media - Chen, Keyin (Transactions on Social Science, Education and Humanities Research, 2024)
Because of the development of social media, depression and anxiety have become hot topics for a long time and the public concentrates on whether they can be treated or not. This article clearly illustrates which factors influence these two symptoms, the consequences that they bring and ways to solve them through a combination of knowledge of social media and psychology. The study of masses and upward social comparison, shows that the increasing popularity of depression and anxiety is due to features of crowds that are infectious, emotional and suggestive. According to a generalized analysis, intimate relationships and social media are beneficial for treating these two mental problems. Intimate relationships mostly occur in schools and daily interpersonal communications. Meanwhile, social networks can produce shelters for people who suffer from exclusion and psychological disorders. However, not only the living environment, but also digital media can damage people a lot. In addition, threats of depression and anxiety include health, social and work issues that can continuously effect the normal progress of work. There are some appropriate strategies to reduce them are restricting the use of social media and social support by the study of Therapy interventions and Stage Environment Matching Theory. To sum up, it is clear that popularity of depression and anxiety can be solved but cannot be treated completely.